Islam and early-stage entrepreneurial activity in Indonesia: religion is not the opium of entrepreneurship - Wijaya, Ibrahim Fatwa; Moro, Andrea; Belghitar, Yacine; Prabowo, Muhammad Agung (Emerald, 2025)
Purpose Our research examines the impact of Islamic religiosity, exploring the role of religious actors, religious ideas (knowledge-based religiosity) and religious practice, on the involvement in early-stage entrepreneurial activity at the provincial level in Indonesia. Design/methodology/approach We rely on the survey conducted by Global Entrepreneurship Monitoring in Indonesia, spanning from 2013 to 2017. The dataset comprises responses from 21,279 individuals. We use probit regression, and the main independent variable, Islamic religiosity, is measured using one factor that incorporates knowledge-based religiosity (extracted relying on Islamic schools, Mosques and Islamic seminaries) and practice-based religiosity (extracted relying on Halal products and Hajj applications). To further explore the role of individual variables, we also estimate the probit regression entering religiosity variables one by one. Our results are robust to endogeneity issues. Findings We find that areas characterised by stronger Islamic religiosity in terms of the presence of actors that disseminate religious ideas and in terms of religious practice have more people involved in early-stage entrepreneurial activity. Originality/value Irrespective of the growing interest in exploring the impact of religiosity on entrepreneurship, there is limited discussion on the impact of Islamic religiosity on entrepreneurial activity.
Keywords: 35 Commerce, Management, Tourism and Services; 3505 Human Resources and Industrial Relations; 3506 Marketing; 3507 Strategy, Management and Organisational Behaviour; Business & Management; Islam; Religiosity; Entrepreneurship; Entrepreneurial activity; Indonesia; L26; Z12